Synthesis Of Mesoporous Silica Nanocomposites For Preparation Of Gold Nanoparticles - Mohamad Azani Jalani; Leny Yuliati; Salasiah Endud; Hendrik Oktendy Lintang (Trans Tech Publications, 2024)
Gold nanoparticles (AuNPs) having particle size less than 10 nm can exhibit enhancement of surface area to give high activity such as in catalytic reaction. However, it is hard to synthesize AuNPs with small particle size due to the strong agglomeration. Herein we report that channels of mesoporous silica synthesized via the template sol-gel synthesis can be used to prepare AuNPs by calcination method. Mesoporous silica with an interpore distance of 4.1 nm was successfully fabricated as transparent thin film by using an amphiphilic trinuclear gold (I) pyrazolate complex as a template for the sol-gel synthesis. Upon calcination at 450 °C for 3 h, silica film nanocomposites showed red-shifting of surface plasmon resonance (SPR) bands from 518 (AuNPs from the bulk) to 544 nm owing to decreasing of the average particle size. The formation of AuNPs was also supported by the appearance of diffraction peaks of d111 at 2θ = 38.20° having a cubic phase. Moreover, transmission electron microscope (TEM) images and X-ray diffraction (XRD) peaks also showed smaller and more homogenous distribution of AuNPs.